Troll Brothers Enterprise / Muhammad Afif Firdaus Mohd Ali...[et al.] - Mohd Ali, Muhammad Afif Firdaus; Hamidi, Mohammad Zulfadli; Sahruddin, Mohd Irfan Hakeem; Hashim, Mohammad Hamizan; Mohd Shafian, Muhamad Zaquan Hakim (2017)
While there are many cement company like us, TROLL BROTHERS will excel due to the customer service provided. Customer satisfaction is our main priority. In order to ensure our customers satisfy with our service, we provide free delivery for the cement and it does not require much time to deliver the cement to them. We also treat our client nicely and they will feel comfortable when negotiating with us since we provided a convenient office. The TROLL BROTHERS ENTERPRISE saw the opportunity that this business has the potential of success if it is handled efficiently. There will be a high demand for cement from many companies since Malaysia is a fast growing country. TROLL BROTHERS ENTERPRISE sees this as a way to prosper in this market, by taking advantage of all these people's need.